Home Cooking and Phenolics: Effect of Thermal Treatment and Addition of Extra Virgin Olive Oil on the Phenolic Profile of Tomato Sauces - Vallverdu-Queralt, Anna; Regueiro, Jorge; Rinaldi de Alvarenga, Jose Fernando; Torrado, Xavier; Lamuela-Raventos, Rosa M. (Amer Chemical Soc, 2014)
Tomato products are a key component of the Mediterranean diet, which is strongly related to a reduced risk of cardiovascular events. The effect of cooking time (15, 30, 45, and 60 min) and the addition of extra virgin olive oil (5 and 10%) on the phenolic content of tomato sauces was monitored using liquid chromatography coupled to tandem mass spectrometry. Concentration of phenolics in the tomato sauces decreased during the cooking process, with the exception of caffeic acid and tyrosol. The main degradation observed was the oxidation of quercetin, since the hydroxy-function at the C-ring of this flavonoid is not blocked by a sugar moiety, unlike rutin. Higher levels of virgin olive oil in tomato sauce seemed to enhance the extraction of phenolic compounds from the tomato, leading to higher phenolic contents in the sauces. Thus, the food matrix containing the phenolic compounds plays a crucial role in determining their accessibility.
Keywords: thermal treatments; cooking effects; polyphenols; food matrix; tomato sauces; extra virgin olive oil; HPLC-MS/MS